2009
DOI: 10.1093/aob/mcp006
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of two Medicago species shaped by distinct life form, mating system and seed dispersal

Abstract: The mating system differentiation estimated from the genetic data is consistent with floral morphology and observed pollinator visitation. There was a much higher historical gene flow in M. ruthenica than in M. lupulina, despite more effective seed dispersal mechanisms in M. lupulina. The population genetic structure and geographical distribution of the two Medicago species have been shaped by life form, mating systems and seed dispersal mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 64 publications
5
34
0
Order By: Relevance
“…Moreover, the coiled pod morphology represents a change in seed dispersal strategies with a likely impact on population structures and fitness (Heyn, 1963;Lesins and Lesins, 1979;Polhill, 1994;Levin et al, 2003;Yan et al, 2009). The possible evolutionary advantages of the novel pod morphology in Medicago spp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the coiled pod morphology represents a change in seed dispersal strategies with a likely impact on population structures and fitness (Heyn, 1963;Lesins and Lesins, 1979;Polhill, 1994;Levin et al, 2003;Yan et al, 2009). The possible evolutionary advantages of the novel pod morphology in Medicago spp.…”
Section: Discussionmentioning
confidence: 99%
“…Gene flow by pollen or seed dispersal, neutral genetic drift and natural selection are among the most important evolutionary forces shaping the genetic diversity of plant populations at different spatial scales (Loveless and Hamrick 1984). Gene flow is strongly dependent on the structure of the landscape, breeding system, pollination vectors and adaptations of seeds for dispersal (Kalisz et al 2001;Gaudeul et al 2007;Yan et al 2009). Since gene flow is more likely among geographically close populations, isolation by distance (IBD; Hutchison and Templeton 1999) can create spatial genetic structure.…”
Section: Introductionmentioning
confidence: 99%
“…It revealed that geographic origin was not related to genotypic similarity among populations. However, in controversial reports, Mengoni et al (2000) and Yan et al (2009) detected the significantly positive correlation between genetic and geographical distances in M. sativa and M. lupulina populations with different geographical origins, respectively. In general they found a tendency for closely situated populations to be genetically more similar.…”
Section: Discussionmentioning
confidence: 86%